2006
DOI: 10.1016/j.febslet.2005.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the taste‐modifying protein, miraculin, in transgenic lettuce

Abstract: Taste-modifying proteins are a natural alternative to artificial sweeteners and flavor enhancers and have been used in some cultures for centuries. The taste-modifying protein, miraculin, has the unusual property of being able to modify a sour taste into a sweet taste. Here, we report the use of a plant expression system for the production of miraculin. A synthetic gene encoding miraculin was placed under the control of constitutive promoters and transferred to lettuce. Expression of this gene in transgenic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 31 publications
0
96
0
13
Order By: Relevance
“…In brief miraculin encoding 660-bp DNA fragment was inserted into the XbaI/SacI sites of the plant transformation vectors pBI121 (Sun et al 2006). Line 56B possesses a single copy of the miraculin gene driven by the CaMV 35S promoter.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief miraculin encoding 660-bp DNA fragment was inserted into the XbaI/SacI sites of the plant transformation vectors pBI121 (Sun et al 2006). Line 56B possesses a single copy of the miraculin gene driven by the CaMV 35S promoter.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Nevertheless, commercial production of miraculin is limited because the natural source is a tropical plant that is difficult to cultivate and is not very productive. Efforts to produce miraculin in other organisms such as Escherichia coli (Kurihara 1992), yeast (Kurihara and Nirasawa 1997), tobacco (Kurihara and Nirasawa 1997), lettuce (Sun et al 2006), tomato (Sun et al 2007), and strawberry (Sugaya et al 2008) have been going on since 1990. Recently, a research group reattempted to produce miraculin in E. coli, but the recombinant protein exhibited lower taste-modifying activity than the native miraculin because the recombinant miraculin was not glycosylated (Matsuyama et al 2009).…”
mentioning
confidence: 99%
“…Recently, however, when Aspergillus oryzae was used as a host for expressing miraculin, the recombinant protein did exhibit taste-modifying properties (Ito et al 2007). We have also successfully expressed recombinant miraculin in seedpropagated crop species, including lettuce (Sun et al 2006) and tomato (Sun et al 2007); however, in subsequent generations, stable miraculin expression was observed in tomato but silencing of the transgene occurred in lettuce, although the recombinant protein was correctly folded in both cases. This suggests that the plant species used for transformation and the mode of seedling propagation are important for producing miraculin-expressing transgenic plants.…”
mentioning
confidence: 99%
“…The content of recombinant VrPDF1 was determined by the ELISA method of Sun et al (2006) [23]. Soluble protein was extracted from T1 generation tobacco transformation seeds and diluted to a concentration of 200 µg ml -1 , and 100 µl VrPDF1 dilution was added into microplates three times.…”
Section: Analysis Of Recombinant Vrdef1 Protein By Western Blot and Ementioning
confidence: 99%